PEMBERDAYAAN POTENSI DESA DAN PENERAPAN TEKNOLOGI PENGERING PADA INDUSTRI TENUN PEWARNA ALAMI DAN KERAJINAN ATE DI DESA SERAYA TIMUR KARANGASEM – BALI - I K. G. Sugita; I G N Priambadi; N Suarnadwipa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The East Seraya village is a village that has some potential to be developed. The economic potential of the village comes from the marine products and the creative industries of weaving and craftsmen of ate. The natural beauty of the village while the potential to be developed as a tourist attraction/ tour support, which is supported by the position of Seraya village located at the tip and the tourist track Amed travel. Weaving craftsmen gathered in a group that named is